The Characterization of Capsule Shell from Acid-Hydrolyzed Palm Oil Starch - Amalia Khairunnisa; Pratika Viogenta; Nani Kartinah; Desy Aulia Azzahra (ALCHEMY Jurnal Penelitian Kimia, 2025)
Acid hydrolysis of palm trunk starch can increase the amylose content in starch, providing a stronger and more stable film. This study aims to obtain the best-modified starch concentration ratio with hydroxypropyl methylcellulose (HPMC) and identify their characteristics. Modifying palm trunk starch was conducted with an acetic buffer using CH3COONa and CH3COOH, decolorizing starch with activated carbon. Manufacturing a capsule shell was performed with weight ratio variations of modified starch and HPMC 1:1 (F1), 2:1 (F2), and 3:1 (F3). All formulations produced firm and elastic capsule shells. The capsule products were consistent in an average weight of F1 (0.10 g), F2 (0.11 g), and F3 (0.14 g). The average disintegration test results were F1 (10 minutes, 27.57 seconds), F2 (6 minutes, 47.06 seconds), and F3 (4 minutes, 34.24 seconds). Tensile strength results were F1 (2.147 MPa), F2 (2.565 MPa), and F3 (2.159 MPa). Fourier Transform Infrared (FTIR) results showed a vibration at a wavenumber of 1560 cm-1 corresponding to the characteristic fingerprint of the C–O vibration stretching in the capsule shell made from starch modified by HPMC. The concentration of modified starch affects the capsule shell’s characteristics, showing that capsule shell F2 (2:1) has the best formulation.